2015
DOI: 10.1007/s10578-015-0536-0
|View full text |Cite
|
Sign up to set email alerts
|

Coparenting Problems with Toddlers Predict Children’s Symptoms of Psychological Problems at Age 7

Abstract: This study examined whether coparenting during toddlerhood predicts children's later symptoms of attention deficit/hyperactivity disorder, oppositional defiant disorder, affective disorder, and somatic complaints. When children were 2 years old, 108 middle-class nonclinical families were observed in triadic interactions to assess two domains of dyadic coparenting (competitive and cooperative), as well as each parent's individual competitive behavior toward the spouse. Teachers and mothers reported children's s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
1
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 49 publications
3
34
1
8
Order By: Relevance
“…Parents were instructed to dress up the child together and to act as they normally would. Clothes changing tasks have been used previously in coparenting research (e.g., Schoppe‐Sullivan et al., ; Umemura, Christopher, Mann, Jacobvitz, & Hazen, ), in order to involve parents in a task that has a joint goal and thereby induces collaboration (Schoppe‐Sullivan et al., ). Parents could freely choose whether they wanted to put the clothes over the child's own clothing or to first undress the child.…”
Section: Methodsmentioning
confidence: 99%
“…Parents were instructed to dress up the child together and to act as they normally would. Clothes changing tasks have been used previously in coparenting research (e.g., Schoppe‐Sullivan et al., ; Umemura, Christopher, Mann, Jacobvitz, & Hazen, ), in order to involve parents in a task that has a joint goal and thereby induces collaboration (Schoppe‐Sullivan et al., ). Parents could freely choose whether they wanted to put the clothes over the child's own clothing or to first undress the child.…”
Section: Methodsmentioning
confidence: 99%
“…Coparenting is conceptualized as exerting, on the one hand, direct influence on children's outcomes (e.g., by jeopardizing coparents' positive coordination in daily childrearing duties and by exposing the child to interparental conflict) and, on the other hand, indirect influence by affecting parents' adjustment and parenting practices, which in turn have impact on children's adjustment. This conceptual hypothesis has been supported by a body of empirical work [13,[18][19][20]. For example, Umemura et al [20] found that competitive coparenting directly predicted externalizing and somatic symptoms in school-aged children, whereas Jones et al [19] found the association between coparenting conflict and children's internalizing and externalizing problems was partially mediated by parenting.…”
Section: Coparentingmentioning
confidence: 96%
“…This conceptual hypothesis has been supported by a body of empirical work [13,[18][19][20]. For example, Umemura et al [20] found that competitive coparenting directly predicted externalizing and somatic symptoms in school-aged children, whereas Jones et al [19] found the association between coparenting conflict and children's internalizing and externalizing problems was partially mediated by parenting.…”
Section: Coparentingmentioning
confidence: 96%
“…Interparental cooperation is theorized to provide the consistency and inter-parental predictability that helps children-particularly younger preschoolers but also burgeoning adolescents-to derive benefit. Indeed, both children's externalizing (Schoppe, Mangelsdorf, & Frosch, 2001;Umemura, Christopher, Mann, Jacobvitz, & Hazen, 2015) and internalizing symptoms (Kolak & Vernon-Feagans, 2008) have been linked to unsupportive coparenting. However, while child problems have typically been cast as sequela or consequences of coparental dysfunction (for a review, see Teubert & Pinquart, 2010), the direction of influence between child problems and coparenting is likely circular rather than linear.…”
Section: Individual and Dyadic Adjustment As Foundations Of Family Lementioning
confidence: 99%